Effectiveness of Intervention with Health (m-Health) Technology for Health Care Compliance: Literature Review - Parwati, Ni Made; Januraga, Pande; Suarjawa, - (Journal of A Sustainable Global South; Vol 4 No 1 (2020): February 2020DO - 10.24843/jsgs.2020.v04.i01.p01, 2020)
The integration of cellular technology in healthcare (M-Health) has the potential in coping with the constraints of the medical service system and to become a breakthrough to support the patients’ medication adherence. This review was conducted to compare and evaluate the effectiveness of M-Healthin terms of the patients’ medication adherence.The literature review conducting  on PubMed, Cochrane Library, Ebsco Health and Taylor & Francis was confined to the articles published between 2010 and 2019. Fifteen articles relating to medication adherence were reviewed, eleven of which employed RCT methods including quasi-experiment that assessed the effectiveness of M-Health to measure the adherence, while four other researches employed qualitative studies to explore patients’ perceptions.The review showed that the intervention of m-Health is effective to drive the compliance of the treatment in accordance with healthcare promotion efforts as well as the prevention, screening and the management of the diseases. Two studies have shown inconsistent results regarding the prevention of obesity and the management of hypertension patients. The development of such model abd the integration of parallel m-Health and healthcare promotion will improve the long-term medication adherence. Index Terms — effectiveness, compliance, M-health, health care